Real-time monitoring of intracellular redox changes in Methylococcus capsulatus (Bath) for efficient bioconversion of methane to methanol. (October 2017) - Ishikawa, Masahito; Tanaka, Yuya; Suzuki, Risa; Kimura, Kota; Tanaka, Kenya; Kamiya, Kazuhide; Ito, Hidehiro; Kato, Souichiro; Kamachi, Toshiaki; Hori, Katsutoshi; Nakanishi, Shuji
Graphical abstract: Highlights: Peredox-mCherry, a fluorescent NADH sensor, was introduced into M. capsulatus . The emitted fluorescence changed accompanying methane metabolism. The OCP measurement confirmed the function of Peredox-mCherry in M. capsulatus . The intracellular NADH state during the bioconversion of methane to methanol was monitored. Abstract: This study aimed to develop a novel method for real-time monitoring of the intracellular redox states in a methanotroph Methylococcus capsulatus, using Peredox as a genetically encoded fluorescent sensor of the NADH:NAD + ratio. As expected, the fluorescence derived from the Peredox-expressing M. capsulatus transformant increased by supplementation of electron donor compounds (methane and formate), while it decreased by specifically inhibiting the methanol oxidation reaction. Electrochemical measurements confirmed that the Peredox fluorescence reliably represents the intracellular redox changes. This study is the first to construct a reliable redox-monitoring method for methanotrophs, which will facilitate to develop more efficient methane-to-methanol bioconversion processes.